Nonlinear Dynamic Modelling and Analysis of a 3-D Overhead Gantry Crane System with System Parameters Variation - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli; Fairuz Rizal, Mohamad Rashidi (United Kingdom Simulation Society, 2010)
Overhead cranes are widely used in industry for transportation of heavy loads. The natural sway of crane payloads is detrimental to safe and efficient operation. However, the crane acceleration, required for motion, always induces undesirable load swing. This paper presents dynamic modelling of a 3-D overhead gantry crane system based on closed-form equations of motion. The Lagrangian method is used to derive the dynamic model of the system. A dynamic model of the system incorporating payload and rope length is developed. Then the effects of payload and rope length on the response of the system are discussed. Extensive results that validate the theoretical derivation are presented in the time and frequency domains.